2019
DOI: 10.31729/jnma.4736
|View full text |Cite
|
Sign up to set email alerts
|

Study of Acid-Base Disorders and Biochemical Findings of Patients in a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Acid base disorder is a condition characterized by alteration in blood pH by theimbalance between the components of blood leading to a life threatening situation. The main aimof this study was to find the prevalence of acid-base disorders and biochemical findings of suchdisorders in patients in a tertairy care hospital. Methods: This descriptive cross-sectional study was conducted in Nobel Medical College TeachingHospital from 1st September, 2018 to 31st August, 2019. Ethical apporoval was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Unfortunately, we only had an ABG analysis available after his presentation; an ABG before admission is best to confirm this hypothesis. Hyperventilation syndrome will often present with dizziness or lightheadedness, paresthesia, palpitations, chest pain or tightness, and, less commonly, carpopedal spasms 2 3. Our patient reported some of these symptoms.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Unfortunately, we only had an ABG analysis available after his presentation; an ABG before admission is best to confirm this hypothesis. Hyperventilation syndrome will often present with dizziness or lightheadedness, paresthesia, palpitations, chest pain or tightness, and, less commonly, carpopedal spasms 2 3. Our patient reported some of these symptoms.…”
Section: Discussionmentioning
confidence: 59%
“…Acid–base disorders (ABDs) are common in hospitalised patients, with a prevalence from 62% to 71% in cross-sectional studies of a pooled population in the intensive care unit (ICU) and emergency department (ED) 1 2. A prospective observational study identified that an elevated serum pH (alkalaemia) was associated with higher levels of morbidity and mortality, with a mortality rate as high as 48.5% in patients with a pH greater than 7.60 3.…”
Section: Introductionmentioning
confidence: 99%